Comprehensive Virology 1980
DOI: 10.1007/978-1-4613-3129-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Defective Interfering RNA Viruses and the Host-Cell Response

Abstract: This chapter will emphasize recently derived knowledge concerning the nature of defective interfering (DI) particles of RNA animal viruses, their biological origins and functions, and their involvement in long-term persistent infections. We will not attempt to review all of the DI literature, and we will confine ourselves to DI particles of RNA viruses. The previous review by Huang and Baltimore (1977) amply documents the occurrence and behavior of DI particles in a wide variety of DNA and RNA viruses and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 186 publications
(238 reference statements)
3
69
0
1
Order By: Relevance
“…We have initiated several IPNV persistently infected CHSE-214 cell lines using either a high DI-producing serotype (OV-3) or a low DI-producing variant of a different serotype (Jasper virus, JV) in order to determine the major characteristics of the virus/cell interaction during long-term persistence. With the exception of a few quantitative differences, we have found that the characteristics of cells persistently infected by either serotype of IPNV conformed to the criteria set forth by Holland et al (1980) for persistent infection involving DI particles.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…We have initiated several IPNV persistently infected CHSE-214 cell lines using either a high DI-producing serotype (OV-3) or a low DI-producing variant of a different serotype (Jasper virus, JV) in order to determine the major characteristics of the virus/cell interaction during long-term persistence. With the exception of a few quantitative differences, we have found that the characteristics of cells persistently infected by either serotype of IPNV conformed to the criteria set forth by Holland et al (1980) for persistent infection involving DI particles.…”
Section: Introductionsupporting
confidence: 50%
“…Since this assay measured a different parameter than the previous (yield/cell) assay, our results suggest that there was a 6-to 60-fold increase in the number of abortive infections with heterologous viruses used at low m.o.i, in IPNV persistently infected cells. Holland et al (1980) have observed that their persistently infected cells could be cured of virus infection only with difficulty by incubation with antiserum. In our system, COV79 cells could be completely cured of virus when cultured in the presence of anti-OV-3 serum.…”
Section: Effect Of Superinfeetion On Persistently Infected Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of DIP may allow animal viruses to potentiate their cytolytic properties and establish persistent infection (Holland et al, 1980). Although plant viruses are not cytolytic and routinely establish permanent infection of their hosts, partial recovery, as evidenced by sharp reductions in infectivity following the initial infection, occurs during infections by lettuce necrotic yellows virus (Crowley et al, 1965), broccoli necrotic yellows virus (Lin & Campbell, 1972), SYNV (Jackson & Christie, 1977;Ismail et al, 1987) and may be a feature of, although not exclusive to, the plant rhabdoviruses (Francki & Randles, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Since these viruses are defective and are unable to replicate unaided, propagation is achieved by co-infecting cells with DI and standard virus. The yield from such co-infected cells contains reduced quantities of standard virus, hence the term interference (Holland et al, 1980;Perrault, 1981). DI viruses have been described for the alphaviruses Sindbis and Semliki Forest (SFV) (Schlesinger et al, 1972;) and the genome has been shown to be smaller (often < 1 × 106) than that of standard virus (4-2 x 106) (Shenk & Stollar, 1972;Eaton & Faulkner, 1973; Weiss & Schlesinger, 1973;Eaton, 1975;Guild & Stollar, 1975;Logan, 1979).…”
Section: Discussionmentioning
confidence: 99%